Aqua(2,2 `-bipyridine-kappa N-2,N `)bis(4-iodobenzoato-kappa O)copper(II) - Mohamadin, M.I.; Abdullah, N.; Lo, K.M.; Ng, S.W. (International Union of Crystallography, 2010)
The Cu-II atom in the title compound, [Cu(C7H4IO2)(2)(C10H8N2)(H2O)], is N,N'-chelated by a 2,2'-bipyridine ligand and is coordinated by two monodentate carboxylate ions and a water molecule in a distorted square-pyramidal geometry. The apical site is occupied by one of the carboxylate O atoms. The water molecule forms intramolecular hydrogen bonds to the uncoordinated carboxyl O atoms. The crystal studied was a nonmerohedral twin with minor components in 0.381 (3) and 0.108 (2) proportions.